ANALISIS PERTANGGUNGJAWABAN ALOKASI DANA DESA (ADD) STUDI PADA DESA LAM ARA DI KECAMATAN BANDA RAYA KOTA BANDA ACEH - Ananda Agusthian; Said Muniruddin (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2020)
The purpose of the research is to describe and analyze accountability village funds allocation in Lam Ara Village. The method used is data analysis with a descriptive qualitative approach. Data collection was taken by interviewing several employees working in the Lam Ara Village Office in Banda Aceh. The results of the study show that  The  accountability  phase  of  the  Village  Fund  Allocation  (ADD)  in  Lam  Ara,  both  technically  and administratively is good, but must still receive guidance from the Banda Aceh City government, Implementation of the use of village funds has applied the principle of accountability. Thus it is necessary to make improvements on an ongoing  basis  while  still  adjusting  the  situation  and  conditions  and  the  development  of  applicable  laws  and regulations